The Leadership of School Principals as Change Agents in Coaching and Development to Influence Teachers' Creative Behavior - Indriasari, Marina; Neng Siska Fitriani; Sysi Jamil Samsiyah (Arbain Publishing, 2025)
The principal’s role as a leader and agent of change is pivotal in influencing teacher performance and advancing educational quality. Beyond administrative responsibilities, principals adopt transformational leadership to inspire innovation, promote creativity, and build a positive school culture. By fostering collaboration, openness, and adaptability, they create environments that drive continuous improvement. Teachers, as the foundation of effective learning, benefit from the principal’s support through motivation, training, and the cultivation of a collaborative work culture. This empowerment enables teachers to develop innovative teaching methods, effectively integrate technology, and enhance student outcomes. Additionally, principals play a crucial role in shaping school norms and values to align with educational goals, cultivating trust and shared leadership while reducing resistance to change. Through valuing creativity and encouraging teacher initiatives, principals strengthen readiness for innovation and ensure schools remain dynamic and forward-looking. This article explores the principal’s role as a transformational leader and agent of change, highlighting their strategies and impact in fostering teacher performance and creating adaptive, innovative, and collaborative educational environments.remain vibrant, innovative, and aligned with the evolving demands of education and society.